2014
DOI: 10.1155/2014/719578
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Relationship between SGLT2 Inhibitors and Cancer

Abstract: Risk of increasing breast and bladder cancer remains a safety issue of SGLT2 (sodium glucose cotransporter type 2) inhibitors, a novel class of antidiabetic agent. We reviewed related papers published before January 29, 2014, through Pubmed search. Dapagliflozin and canagliflozin are the first two approved SGLT2 inhibitors for diabetes therapy. Although preclinical animal toxicology did not suggest a cancer risk of dapagliflozin and overall tumor did not increase, excess numbers of female breast cancer and mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 49 publications
3
64
2
3
Order By: Relevance
“…As such women and men should be taught the benefits of good perineal hygiene and may even benefit from prophylactic therapy (7)(13). Importantly, while SGLT2i therapy predicates on diuresis to remove the additional glucose load the frequency of hypotensive episodes occur in only 1.2-1.3% of patients with no significant impact noted on the rate ofvenous thromboembolism events (10) Of some concern, observational studies have highlighted a trend to increased incidence of particularly bladder cancer in the long-term use of dapagliflozin (17). However this on further study has been found to not be significant as dapagliflozin has not been found to affect bladder cancer cell growth or survival.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such women and men should be taught the benefits of good perineal hygiene and may even benefit from prophylactic therapy (7)(13). Importantly, while SGLT2i therapy predicates on diuresis to remove the additional glucose load the frequency of hypotensive episodes occur in only 1.2-1.3% of patients with no significant impact noted on the rate ofvenous thromboembolism events (10) Of some concern, observational studies have highlighted a trend to increased incidence of particularly bladder cancer in the long-term use of dapagliflozin (17). However this on further study has been found to not be significant as dapagliflozin has not been found to affect bladder cancer cell growth or survival.…”
Section: Resultsmentioning
confidence: 99%
“…However this on further study has been found to not be significant as dapagliflozin has not been found to affect bladder cancer cell growth or survival. Moreover, it has been found that SGLT1 is over expressed in many cancer types and its inhibition has been found to sensitize prostatic cancer cells to monoclonal and Tyrosine Kinase based therapy and in pancreatic adenocarcinoma significantly correlates with disease free survival (17).…”
Section: Resultsmentioning
confidence: 99%
“…As for pioglitazone, the potential cardiovascular benefit from the proactive study must be balanced against the documented increase of bladder cancer risk, a controversial and not fully understood adverse reaction also reported with gliflozins (especially dapagliflozin) [10]. Accordingly, the current European summary of product characteristics does not recommend the association of SGLT-2 inhibitors with pioglitazone as a precautionary measure [11].…”
Section: Non-inferiority Achievedmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][10][11][12][13][14][15][16][17][18][19] Moreover, the long term consequences of persistent exposure of urinary tract including urinary bladder to hyperglycemic hypertonic urine are unknown although increased risk of bladder cancer has been reported. 19,20 I believe that constant presence of sugar, the most efficient fuel for cell growth may have promoted growth of bladder cancer in situ and rendered it to be manifested rather than initiating the onset.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28] Severe hypercalcemia and hypernatremia may be attributed to dehydration and increase in uric acid excretion may be responsible for hypouricemia. Hypophosphatemia was secondary to phosohaturia and anion gap acidosis may be attributed to amino aciduria both being the characteristic manifestations of Fanconi Syndrome, a renal tubular defect which also caused proteinuria in this patient within a week of administration of Canagliflozin.…”
Section: Introductionmentioning
confidence: 99%